Utilization of Reading Corners in Literacy Activities to Improve Likes to Read Character and Reading Ability of Elementary School Students - Widyami, GA Putu Ayu Suci; Sudiana, I Nyoman; Putrayasa, lda Bagus (Universitas Pendidikan Ganesha, 2023)
Literacy activities are carried out through habituation activities for all students in the school environment. The lack of use of reading corners makes literacy learning achievements not as expected. This study aims to explore the implementation of the reading corner program, literacy activities, reading skills, and the character of fond of reading elementary school students. This type of research is descriptive explorative with a qualitative approach. Data was collected through interviews, observation, and documentation. The results of the study show that the reading corner program is part of the Bali Danu program, which is an attempt to update the previous program. The collection of books in the reading corner is used as reading material for school literacy activities, and educators use the reading corner as a place for discussion and self-development for students, especially in reading and storytelling activities. Through regular literacy activities and reading corners, students' reading skills and liking to read can be improved. In addition to using the reading corner as a place to read books, the reading corner becomes their class identity; there is a sense of belonging to the reading corner because students are directly involved in creating and maintaining the reading corner.